The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.3389/fmicb.2015.00229
|View full text |Cite
|
Sign up to set email alerts
|

rpoN1, but not rpoN2, is required for twitching motility, natural competence, growth on nitrate, and virulence of Ralstonia solanacearum

Abstract: The plant pathogen Ralstonia solanacearum has two genes encoding for the sigma factor σ54: rpoN1, located in the chromosome and rpoN2, located in a distinct “megaplasmid” replicon. In this study, individual mutants as well as a double mutant of rpoN were created in R. solanacearum strain GMI1000 in order to determine the extent of functional overlap between these two genes. By virulence assay we observed that rpoN1 is required for virulence whereas rpoN2 is not. In addition rpoN1 controls other important funct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
52
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(56 citation statements)
references
References 49 publications
2
52
0
Order By: Relevance
“…Ray et al . () revealed the broad conservation and stability of rpoN2 in the R. solanacearum species complex. They speculated that rpoN2 might be involved in the adaptation of the bacterium to a specific niche or environmental condition during its life cycle.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Ray et al . () revealed the broad conservation and stability of rpoN2 in the R. solanacearum species complex. They speculated that rpoN2 might be involved in the adaptation of the bacterium to a specific niche or environmental condition during its life cycle.…”
Section: Discussionmentioning
confidence: 99%
“…r54 (rpoN) is involved in the regulation of nitrogen metabolism, and subsequently affects many other biological activities in diverse Proteobacteria (Buck et al, 2000). In R. solanacearum, RpoN1, but not RpoN2, helps to regulate the transcription of twitching motility-related genes, and affects the nitrate assimilation pathway and virulence (Ray et al, 2015). Furthermore, rpoN2 expression is dependent on rpoN1.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has also been revealed that some bacteria, including Xanthomonas oryzae pv. oryzae, Bradyrhizobium japonicum, Rhizobium etli, Burkholderia fungorum, and Ralstonia solanacearum, carry two copies of rpoN (31)(32)(33)(34), and four copies of rpoN are encoded in the genome of Rhodobacter sphaeroides (35). The four paralogues were designated rpoN1, rpoN2, rpoN3, and rpoN4, and their GϩC contents were 68.29%, 68.48%, 69.57%, and 56.13%, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…The motility of R. solanacearum is reflected in two aspects: swimming motility and twitching motility. Swimming motility is controlled only by flagellum, but flagellum formation and movement in R. solanacearum are regulated by very complex genes and are influenced by cell concentrations and other signalling molecules, such as nitrate (Dalsing & Allen, ; Ray, Kumar, Peeters, Boucher, & Genin, ; Tans‐Kersten, Brown, & Allen, ). In general, changes in mobility contribute to the adaptation of R. solanacearum to a variety of environments.…”
Section: Discussionmentioning
confidence: 99%